2010
DOI: 10.1002/jbm.a.32724
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of formulation parameters affecting low molecular weight drug release from in situ forming drug delivery systems

Abstract: In situ forming implants (ISFI) have shown promise in delivering adjuvant chemotherapy following minimally invasive cancer therapies such as thermal ablation of tumors. While ISFI systems have been thoroughly investigated for delivery of high molecular weight (Mw) therapeutics, little research has been conducted to optimize their design for delivery of low Mw drugs. This study examined the effect of varying the formulation components on the low Mw drug release profile from a ISFI consisting of poly(D,L-lactide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 30 publications
8
74
0
2
Order By: Relevance
“…However, high burst levels of NMP could potentially lead to toxic elevated concentrations of NMP. The amount of NMP burst increased with higher molecular weight, which corresponds to other studies that show greater burst release of small molecule drugs with higher molecular weight polymers [31,32]. Prior research has indicated that ISFIs that undergo fast phase separation result in a more porous morphology that accelerates initial release [16,30,33,34].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, high burst levels of NMP could potentially lead to toxic elevated concentrations of NMP. The amount of NMP burst increased with higher molecular weight, which corresponds to other studies that show greater burst release of small molecule drugs with higher molecular weight polymers [31,32]. Prior research has indicated that ISFIs that undergo fast phase separation result in a more porous morphology that accelerates initial release [16,30,33,34].…”
Section: Discussionsupporting
confidence: 75%
“…A major contributing factor to the rate of phase inversion is the hydrophobicity of the polymer with a lower water affinity leading to more rapid phase transitions. Higher molecular weight polymers have been demonstrated to have lower water solubility, indicating that they are more hydrophobic [31], which can explain the relationship between burst and molecular weight demonstrated here. The higher burst rate of polymers with higher lactide content, which agrees with literature [27], can also be attributed to hydrophobicity.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, an increasing number of new active pharmaceutical 70 ingredients belong to the family of peptides or proteins and suffer 71 from low bioavailability after oral administration. Alternative routes of 72 administration (pulmonary, nasal, buccal, transdermal, ocular, and 73 rectal) have also shown drawbacks such as enzymatic degradation or 74 low/variable absorption [1]. As a result, there is a renewed interest in 75 parenteral administration, especially as many improvements have 76 been done in pain reduction.…”
mentioning
confidence: 99%
“…Implants with low MW (intrinsic viscosity 0.3) polymer show multiple pores which account for the rapid solvent exchange while these pores decrease in number and size with high MW (intrinsic viscosity 0.7) polymer. This effect was also illustrated by Patel et al who showed that SEM micrographs of implant cross sections prepared with lower MW PLGA were more porous than their corresponding higher MW PLGA implants [38]. …”
Section: Plga Concentration and Molecular Weight (Intrinsic Viscosity)mentioning
confidence: 54%
“…Exactly at the end of the 4-day time point, in situ forming implants with 1 % and 2.5 % P85 released about 33.6 % and 28.2 %, respectively, of their drug when compared with the corresponding formulations without any P85 (38.2 %). They also stated that increasing the concentration of P85 beyond 5 % reversed any lowering of the drug burst release [38]. DesNoyer and McHugh studied the effect of variations in Pluronic concentration and MW on protein release from PLGA/NMP solutions.…”
Section: Addition Of Plasticizers or Surfactantsmentioning
confidence: 99%